Association of MHC-I genotypes with disease progression in HIV/SIV infections - Nomura, Takushi; Matano, Tetsuro (Frontiers in Microbiology, 2012)
Virus-specific cytotoxic T lymphocytes (CTLs) are major effectors in acquired immune　responses against viral infection. Virus-specific CTLs recognize specific viral peptides　presented by major histocompatibility complex-class I (MHC-I) on the surface of　virus-infected target cells via their T cell receptor and eliminate target cells by both direct and　indirect mechanisms. In human immunodeficiency virus (HIV) and simian immunodeficiency　virus (SIV) infections, host immune responses fail to contain the virus and allow persistent　viral replication, leading to AIDS progression. CTL responses exert strong suppressive　pressure on HIV/SIV replication and cumulative studies have indicated association of　HLA/MHC-I genotypes with rapid or slow AIDS progression.